Crystallization and preliminary X-ray diffraction studies on a recombinant isopenicillin N synthase from Cephalosporium acremonium. - Fujishima, Y; Nordlund, P; Pelosi, G; Schofield, C; Cole, S; Baldwin, J; Hajdu, J (1994)
Recombinant isopenicillin N synthase from Cephalosporium acremonium was expressed in Escherichia coli and the protein was purified. After nearly 5000 crystallization trials, the apo enzyme was crystallized by the hanging drop vapour diffusion technique, using polyethylene glycol and lithium sulphate as precipitants. Two crystal forms have been obtained with either octahedral or elongated prismatic habits. The larger octahedral crystals (0.1 mm over-all dimensions) belong to space group I4 with unit cell dimensions of a = b = 124.7 A, c = 156.9 A, and diffract X-rays to about 3.5 A resolution at synchrotrons. The crystallographic asymmetric unit contains a dimer.